Graphene Based Copper‐Nickel Bimetal Nanocomposite: Magnetically Separable Catalyst for Reducing Hexavalent Chromium. Issue 11 (17th March 2020) - Yao, Dachuan; Xu, Tingting; Yuan, Jingjing; Tao, Yingrui; He, Guangyu; Chen, Haiqun
Abstract: Graphene based copper‐nickel bimetal nanocomposite (Cu3 Ni2 ‐rGO) was prepared via a one‐step solvothermal procedure, in which Ni(OH)2 and Cu(OH)2 were used as precursors. Structural characterization confirms that the as‐prepared Cu3 Ni2 ‐rGO nanocomposite is composed of Cu3 Ni2 nanoparticles in the size range of 20–100 nm and the reduced graphene oxide (rGO) sheets. Benefiting from the combination of Cu3 Ni2 and rGO, the Cu3 Ni2 ‐rGO nanocomposite exhibits excellent catalytic performance on reducing highly toxic Cr(VI) at room temperature. The reduction of Cr(VI) (40 mL, 100 mg L −1 ) can be completed within 6 min using Cu3 Ni2 ‐rGO nanocomposite as the catalyst, which is much more efficient than using monometallic nanocomposite containing only Cu or Ni. Moreover, Cu3 Ni2 ‐rGO nanocomposite can be magnetically separated, which enables effective recycle. Besides, Cu3 Ni2 ‐rGO shows good cycling stability. Abstract : In general, through a low‐cost and simple one‐step solvothermal method, the Cu3 Ni2 ‐rGO nanocomposite was successfully synthesized. The reduction from GO to rGO as well as the growth of Cu3 Ni2 bimetal nanoparticles was accomplished synchronously. The nanocomposite possessing an excellent catalytic performance can perform stably at room temperature when HCOOH is present